Deradicalisation and Disengagement from Terrorism and Threat to Identity: An Analysis of Former Jihadist Prisoners' Accounts. (September 2019) - Syafiq, Muhammad
This qualitative study aims to explore the personal experience of former prisoners jailed for terrorism-related offenses in Indonesia who have reported or have been reported as having deradicalised or disengaged from violent extremism. The participants were interviewed about their experiences of deradicalisation and disengagement and the perceived implication of the experiences on their identities. Data were collected through semistructured interviews and analysed using a thematic analysis. The results show that most participants reported that they experience identity threats because of their status as former terrorist prisoners from former comrades as well as from the wider society. The threats were said to have impacted negatively upon their positive sense of self; thus, they invoked the strategies to cope with the threats. While participants' strategies to cope with former jihadist comrades' threats operated in the intrapersonal level, their strategies to alleviate the threats from wider society occur in the interpersonal level. This study found that most participants re-evaluate their past experiences positively and even utilised them as a part of their present identities primarily when they dealt with former comrades' criticisms. To resist the wider society's stigma and suspicion, they concealed their identity as a former terrorist prisoner while, at the same time, bolstered their personal characteristics in terms of interpersonal relationships.